"They Were Laughing": Congressional Framing of Dr. Christine Blasey Ford's Sexual Assault Allegations on Twitter. (March 2022) - Wright, Jamie M.; Clark, Jennifer Hayes; Evans, Heather K.
Allegations of sexual assault and violence engulfed the confirmation hearings surrounding President Trump's Supreme Court nominee (and now Justice) Brett Kavanaugh. Our work examines congressmembers' communication concerning sexual assault and #MeToo during this critical time of the Kavanaugh hearing and how this relates to perceptions of gender and partisanship today. While previous research demonstrated a strong role of gender in influencing which members discussed #MeToo, we show that partisanship played a much larger role in discussions of sexual assault during this hearing. The findings highlight the shifting narrative surrounding the #MeToo movement and how the multiple identities of members of Congress, namely partisanship and gender, can be activated and produce changes in how elites communicate about the issue, which may have broader policymaking implications.